PHONOLOGICAL VARIABILITY IN MODERN ENGLISH: A LINGUISTIC ANALYSIS OF REGIONAL ACCENTS - Abduraxmanova , Shahzoda (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article analyzes phonological variation in contemporary English from a sociolinguistic perspective. The study examines key phonetic and phonological features of regional accents, including rhoticity, vowel shifts, T-glottalization, and prosodic elements such as rhythm and intonation. It also explores the impact of globalization, urbanization, and digital communication on modern English pronunciation. The findings demonstrate that phonological variation is not random but a systematic phenomenon influenced by social, cognitive, and communicative factors. The research contributes to the fields of sociolinguistics, English language teaching, and intercultural communication. Keywords: phonological variation, accent, dialect, sociolinguistics, vowel shifts, rhoticity, intonation